Specificity of Mercury Detecting Reagents for Skin Lightening Creams - Liliek Nurhidayati; Titiek Martati; I Wayan Redja; Nofanti Sandra (Fakultas Farmasi Universitas Pancasila, 2018)
Inorganic mercury compound have been used for long time in cosmetics preparations for its skin lightening effect. The used of mercury in cosmetics has been prohibited as stipulated in the decision of the BPOM RI (Head of the Food and Drug Supervisory Agency) No.HK.00.01.432.6147. Based on health department research from various countries, there are a number of skin lightening products containing mercury between 660-57.000 μg/kg. People needs a quick and easy way to detect mercury in a lightening cream, so that people can test the safety of cream that used. One alternative that can be used to detect mercury in skin lightening cosmetics is using detecting reagents. The aim of this study was preparation of specific and sensitive mercury detecting reagents. The detecting reagents consisted mixtures of diphenylcarbazone and acetic acid in 96% of ethanol. The specificity test is performed by adding diphenylcarbazone solution into a lightening cream containing whitening agents such as mercury, hydroquinone, bangkuang extract and mixture of these substances. Assay was also performed on simulated cream that contained mercury, zinc oxide, bismuthsubnitrate, and mixture of mercury, zinc oxide and bismuthsubnitrate. The mercury detecting reagents gives a distinctive result that shown by the formation of purple mercury complex in less than 3 minutes.